Comprehensive spectroscopy and photocatalytic activity analysis of TiO2-Pt systems under LED irradiation - Adam Kubiak (Scientific Reports, 2024)
Abstract This study presents a thorough spectroscopic analysis of TiO2-Pt systems under LED irradiation, with a focus on elucidating the photodeposition process of Pt nanoparticles onto TiO2 surfaces. The methodology leverages an innovative LED photoreactor tailored to a specific spectral range, enabling precise characterization of the excitation spectrum of TiO2-Pt composites. Through the identification of Pt precursor species and their excitation under LED-UV light, a photodeposition mechanism is proposed involving concurrent excitation of both the TiO2 semiconductor and the H2PtCl6 precursor. The LED photoreactors are employed to scrutinize the excitation profile of TiO2-Pt materials, revealing that the incorporation of Pt nanoparticles does not expand TiO2's absorption spectrum. Furthermore, UV-A exposure in the absence of Pt did not induce the formation of surface defects, underscoring the lack of visible light activity in TiO2-Pt systems. Spectroscopic analyses, complemented by naproxen photooxidation experiments, indicate the absence of a significant plasmonic effect in Pt nanoparticles within the experimental framework. Mass spectroscopy results corroborate the presence of distinct naproxen degradation pathways, suggesting minimal influence from photocatalyst properties. This research provides a detailed spectroscopic insight into TiO2-Pt photocatalysis, enriching the knowledge of photocatalytic materials in LED lighting.